Long noncoding RNAs Colorectal Neoplasia Differentially Expressed and taurine-upregulated gene 1 are downregulated in sepsis and positively regulate each other to suppress the apoptosis of cardiomyocytes. Issue 2 (20th December 2021) - Xu, Zhenwei; Lin, Xingyu; Zhu, Jingfa; Zhu, Zhixia
ABSTRACT: Long noncoding RNAs (lncRNAs) Colorectal Neoplasia Differentially Expressed (CRNDE) and taurine-upregulated gene 1 (TUG1) play similar roles in sepsis, indicating the existence of the crosstalk between them. Sepsis is a major cause of injuries in heart, which are related to high mortality rates. This study was therefore carried out to analyze the potential crosstalk between CRNDE and TUG1 in sepsis, with a focus on sepsis-induced cell apoptosis in heart. Expression of CRNDE and TUG1 was analyzed with RT-qPCR. Correlations between them were analyzed by Pearson's correlation coefficient. CRNDE and TUG1 were overexpressed in cardiomyocytes to determine the relationship between them. The roles of CRNDE and TUG1 in regulating the apoptosis of cardiomyocytes were explored by cell apoptosis assay. We found that both CRNDE and TUG1 were downregulated in sepsis. In cardiomyocytes, LPS treatment resulted in the downregulation of CRNDE and TUG1. Overexpression of CRNDE and TUG1 in cardiomyocytes increased the expression levels of each other. Under lipopolysaccharide (LPS) treatment, decreased apoptosis rates of cardiomyocytes were observed after CRNDE and TUG1 overexpression. CRNDE and TUG1 co-overexpression showed a stronger effect. In conclusion, CRNDE and TUG1 are downregulated in sepsis and they positively regulate each other to suppress the apoptosis of cardiomyocytes.